Gas permeability study of amine-polymer blend membranes to separate carbondioxide from natural gas - Mushtaq, A. (Trans Tech Publications Ltd, 2014)
The confinement and storage of carbon dioxide has been acknowledged as a prospective solution towards the greenhouse gas effect which in turn cause climate change. Proficient separation technologies are required for removal of carbon dioxide from natural gas streams to allow this solution to be extensively feasible. An emerging technology is the membrane gas separation, which is more dense, energy efficient and possibly more economical than older technologies, such as solvent absorption. Amine has a natural affinity for both carbon dioxide and hydrogen sulphide, allowing it to be a very effective removal process. In this context blending of glassy polymer that is polysulfone and amines, which are diethanol amine, methyl diethanol amine, mono ethanol amine in dimethyl acetamide solvent, flat sheet membranes were developed with desirable properties. Gas permeability study of PSU with amines, blend membranes were evaluated using pure gas CO2 and CH4 at different feed pressures. Â© 2014 Trans Tech Publications, Switzerland.